Based on digital intelligence: teaching innovation and practice of veterinary internal medicine in China’s southwest frontier - Li, Meiquan; Wang, Xiao; Du, Yanli; Zhang, Hongyan; Liao, Bo (Frontiers in Veterinary Science, 2025)
Veterinary internal medicine is a core discipline in animal medicine, crucial for advancing the livestock industry. Nevertheless, conventional teaching methods often suffer from fragmented content, inadequate clinical exposure, and a disconnect from industry requirements. In response, reforms guided by the principle of “integrating knowledge with practice and harmonizing learning with application” are increasingly adopting digital and intelligent technologies. Key innovations include the use of AI-based knowledge graphs to reorganize curricula into a three-phase virtual-real closed-loop system, enabling blended online-offline instruction. This structure supports the integration of theoretical learning, virtual simulation, and clinical application through case analyses, practical exercises, and collaborative discussions. Additionally, virtual simulation platforms and academic-industry partnerships provide holistic training via intelligent case studies and realistic scenario simulations, enhancing clinical reasoning and operational skills. A multidimensional dynamic assessment system has also been introduced, incorporating process-oriented and multi-source evaluations. This system blends online and offline components, integrates corporate feedback, embeds public health and ideological education, and employs blockchain-based micro-credentials to certify competencies. These developments contribute to improved diagnostic decision-making and professional aptitude, while also facilitating the digital transformation of the livestock sector by cultivating skilled, innovative practitioners.